2018
DOI: 10.3390/catal8110503
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Dimensional Numerical Assessment of Heterogeneity Impact on a Solid Oxide Fuel Cell’s Anode Performance

Abstract: In this research, a fully three-dimensional, multiphase, microstructure-scale heterogeneous (non-continuous) electrode, Solid Oxide Fuel Cell (SOFC) stack model is implemented in order to assess the impact of homogeneity disturbance in an SOFC anode. The Butler–Volmer model is combined with recent empirical relations for conductivity and aspects of the Maxwell–Boltzmann kinetic theory describing the transport of mass within the porous medium. Methods for the localized quantification of electrode morphology par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The phase interface area in the case of the cathode was computed using the marching cube method. For details regarding microstructure quantification, see our previous articles [27,28].…”
Section: Microstructure Quantificationmentioning
confidence: 99%
“…The phase interface area in the case of the cathode was computed using the marching cube method. For details regarding microstructure quantification, see our previous articles [27,28].…”
Section: Microstructure Quantificationmentioning
confidence: 99%
“…Their findings demonstrated that MOOSE framework [23] yields a notable improvement in the efficiency of highperformance computing applied to microstructures in SOFC. Despite the large number of research that has been done on microscale physical modeling of SOFC [20,21,22,23,24,25,26,27], mostly are focused on conventional microstructure designs whose 3D reconstructions are acquired with tomography methods (FIB-SEM in particular). The potential of more ordered microstructure configurations, distinct from conventional structures typically produced through tape casting [28], powder ball milling [29], or screen printing [30], remains largely unexplored in this context.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the SOFC electrode is characterized by high internal complexity. In this respect, the electrode's ability to effectively transport the species to and from the reaction site, described by its microstructure's morphological parameters, is of great significance for the cell's overall performance [4,5]. Elaboration of those parameters, like porosity, connectivity, or triple-phase boundary density (reaction domain), becomes a crucial part of any SOFC analysis [6,7].…”
Section: Introductionmentioning
confidence: 99%